Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the system of equations graphically and algebraically, we can follow these steps:
1. Graph the first equation:
[tex]\[ y = 3x + 9 \][/tex]
The equation [tex]\( y = 3x + 9 \)[/tex] is a linear equation in slope-intercept form [tex]\( y = mx + b \)[/tex], where [tex]\( m = 3 \)[/tex] is the slope and [tex]\( b = 9 \)[/tex] is the y-intercept.
- To plot this line, start by locating the y-intercept (0, 9) on the graph.
- From the y-intercept, use the slope. Since the slope is 3, which means "rise over run" is 3/1, move up 3 units and 1 unit to the right to find another point on the line. Repeat this process to draw the line.
2. Graph the second equation:
[tex]\[ 6x + 2y = 6 \][/tex]
To write this in slope-intercept form [tex]\( y = mx + b \)[/tex], solve for [tex]\( y \)[/tex]:
[tex]\[ 2y = -6x + 6 \][/tex]
[tex]\[ y = -3x + 3 \][/tex]
This second linear equation, [tex]\( y = -3x + 3 \)[/tex], has a slope [tex]\( m = -3 \)[/tex] and a y-intercept [tex]\( b = 3 \)[/tex].
- To plot this line, start by locating the y-intercept (0, 3) on the graph.
- From the y-intercept, use the slope. Since the slope is -3, move down 3 units and 1 unit to the right, or equivalently, move up 3 units and 1 unit to the left to find another point on the line. Repeat this process to draw the line.
3. Find the intersection point:
The solution to the system of equations is the point where the two lines intersect.
4. Solving algebraically:
Let's solve the system of equations algebraically to confirm the graphical intersection point.
[tex]\[ y = 3x + 9 \quad \text{(Equation 1)} \][/tex]
[tex]\[ 6x + 2y = 6 \quad \text{(Equation 2)} \][/tex]
Substitute [tex]\( y \)[/tex] from Equation 1 into Equation 2:
[tex]\[ 6x + 2(3x + 9) = 6 \][/tex]
Simplify:
[tex]\[ 6x + 6x + 18 = 6 \][/tex]
[tex]\[ 12x + 18 = 6 \][/tex]
Subtract 18 from both sides:
[tex]\[ 12x = -12 \][/tex]
Divide by 12:
[tex]\[ x = -1 \][/tex]
Substitute [tex]\( x = -1 \)[/tex] back into Equation 1 to find [tex]\( y \)[/tex]:
[tex]\[ y = 3(-1) + 9 \][/tex]
[tex]\[ y = -3 + 9 \][/tex]
[tex]\[ y = 6 \][/tex]
Thus, the solution to the system is the point [tex]\( (-1, 6) \)[/tex].
Therefore, the correct answer to the question is:
There is one unique solution [tex]\((-1,6)\)[/tex].
1. Graph the first equation:
[tex]\[ y = 3x + 9 \][/tex]
The equation [tex]\( y = 3x + 9 \)[/tex] is a linear equation in slope-intercept form [tex]\( y = mx + b \)[/tex], where [tex]\( m = 3 \)[/tex] is the slope and [tex]\( b = 9 \)[/tex] is the y-intercept.
- To plot this line, start by locating the y-intercept (0, 9) on the graph.
- From the y-intercept, use the slope. Since the slope is 3, which means "rise over run" is 3/1, move up 3 units and 1 unit to the right to find another point on the line. Repeat this process to draw the line.
2. Graph the second equation:
[tex]\[ 6x + 2y = 6 \][/tex]
To write this in slope-intercept form [tex]\( y = mx + b \)[/tex], solve for [tex]\( y \)[/tex]:
[tex]\[ 2y = -6x + 6 \][/tex]
[tex]\[ y = -3x + 3 \][/tex]
This second linear equation, [tex]\( y = -3x + 3 \)[/tex], has a slope [tex]\( m = -3 \)[/tex] and a y-intercept [tex]\( b = 3 \)[/tex].
- To plot this line, start by locating the y-intercept (0, 3) on the graph.
- From the y-intercept, use the slope. Since the slope is -3, move down 3 units and 1 unit to the right, or equivalently, move up 3 units and 1 unit to the left to find another point on the line. Repeat this process to draw the line.
3. Find the intersection point:
The solution to the system of equations is the point where the two lines intersect.
4. Solving algebraically:
Let's solve the system of equations algebraically to confirm the graphical intersection point.
[tex]\[ y = 3x + 9 \quad \text{(Equation 1)} \][/tex]
[tex]\[ 6x + 2y = 6 \quad \text{(Equation 2)} \][/tex]
Substitute [tex]\( y \)[/tex] from Equation 1 into Equation 2:
[tex]\[ 6x + 2(3x + 9) = 6 \][/tex]
Simplify:
[tex]\[ 6x + 6x + 18 = 6 \][/tex]
[tex]\[ 12x + 18 = 6 \][/tex]
Subtract 18 from both sides:
[tex]\[ 12x = -12 \][/tex]
Divide by 12:
[tex]\[ x = -1 \][/tex]
Substitute [tex]\( x = -1 \)[/tex] back into Equation 1 to find [tex]\( y \)[/tex]:
[tex]\[ y = 3(-1) + 9 \][/tex]
[tex]\[ y = -3 + 9 \][/tex]
[tex]\[ y = 6 \][/tex]
Thus, the solution to the system is the point [tex]\( (-1, 6) \)[/tex].
Therefore, the correct answer to the question is:
There is one unique solution [tex]\((-1,6)\)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.